Transparency, consent and trust in the use of customers' data by an online genetic testing company: an Exploratory survey among 23andMe users. Issue 4 (1st October 2020) - Raz, Aviad E.; Niemiec, Emilia; Howard, Heidi C.; Sterckx, Sigrid; Cockbain, Julian; Prainsack, Barbara
Abstract : 23andMe not only sells genetic testing but also uses customer data in its R&D activities and commercial partnerships. This raises questions about transparency and informed consent. Based on a online survey conducted in 2017–18, we examine attitudes of 368 customers of 23andMe toward the company's use of their data. Our findings point at divides in the context of customers' awareness of the two-sided business model of DTC genetics and their attitudes toward consent. While most of our respondents (68%) were aware that 23andMe could store their data and use it for certain purposes without their consent, over 40% were not aware that using and sharing customer data was part of the business model. Views were also divided regarding what type of consent was most appropriate. We explore the implications of these divides for participatory research and for the importance of transparency and trust in commercially-driven scientific knowledge production.